Herodotus : A Very Short Introduction - Roberts, Jennifer Tolbert, 1947- (Oxford, New York Oxford University Press, 2011)
Jennifer Roberts introduces the background and writing of the 5th century Greek thinker and researcher Herodotus of Halicarnassus, who invented the genre of historical investigation. She discusses all aspects of his work, including his fascination with his origins; his travels; his interest in seeing the world; and the recurring themes of his work.
Include Index and Illustration
Keywords: Herodotus -- History (Herodotus) -- Greece